Innovation of Red Bean Flour as A Substitution for Wheat Flour in Making Noodle - Rahmawati, Tessa Yulia Hilda; Hermawan, Budi; Witara, I Made; Yuliyanto, Gunawan; Nugroho, Setyo Prasiyono (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2023)
Red bean flour is a type of legume that has many benefits for the body, it's just that its use is not optimal. In this experiment, the researchers innovated noodles by changing the main ingredient with red bean flour. This study aims to find out, 1) How to properly process red bean flour in processed red bean noodles. 2) Can red bean flour be used as a substitute for wheat flour in making noodles. 3) How is the consumer response to aspects of taste, color, texture and aroma of red bean flour noodles. Data collection methods used by researchers are questionnaires, literature studies, and interviews. The test method in this study uses organoleptic testing and the data obtained will have problems in the frequency distribution of the data. The results showed that the cooking methods and procedures for red bean flour noodles and wheat flour noodles had differences. This difference is based on processing methods and processing procedures. The first experiment required an additional ingredient as an adhesive, the second experiment had good results but required an adhesive other than wheat flour, the third experiment required an unsuitable adhesive material, the fourth experiment required the addition of the composition of the ingredients, changes in cooking methods and procedures. The fifth experiment of noodles produced was good and fulfilled standard noodles in general. Based on the results of organoleptic testing of noodles in this study, the taste assessment of wheat flour noodles has a rating of 3.1. while the taste assessment of red bean flour noodles was 3. The assessment of the color aspect of wheat flour noodles had a rating of 2.9. while the color assessment of red bean flour noodles was 2.6. Assessment of the texture aspect of wheat flour noodles has a rating of 2.9. while the texture assessment of red bean flour noodles was 2.8. Assessment of the aroma aspect of wheat flour noodles has a rating of 2.9. while the aroma rating of red bean flour noodles is 3. From the assessment above, in terms of quality, the aspects of taste, color, aroma, texture of red flour noodles are the same as wheat flour noodles.